2019
DOI: 10.1002/ptr.6372
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Lipopolysaccharides‐mediated injury to chondrogenic ATDC5 cells can be relieved by Sinomenine via downregulating microRNA‐192

Abstract: Sinomenine (SIN) is an isoquinoline derived from Caulis Sinomenii that has been used to treat rheumatoid arthritis and osteoarthritis for several decades in China. This study aims to reveal the effects of SIN on mouse chondrogenic ATDC5 cells growth and inflammation. SIN was used to treat ATDC5 cells injured by lipopolysaccharides (LPS). The following parameters were determined for evaluating the treatment effects of SIN: cell viability, apoptosis, reactive oxygen species generation, and pro‐inflammatory cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
(61 reference statements)
0
7
0
Order By: Relevance
“…(2). Sinomenine [133][134][135][136][137][138] (1). -anti-inflammatory [128,131], (i) Antifibrosis [128], (ii) Immuno-suppressive [130], (iii) Suppressed excessive granulocyte activation [129], (iv) Inhibited migration and invasion of fibroblast-like synoviocytes [132], (v) Ameliorated arthritis symptoms [131]; (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2). Sinomenine [133][134][135][136][137][138] (1). -anti-inflammatory [128,131], (i) Antifibrosis [128], (ii) Immuno-suppressive [130], (iii) Suppressed excessive granulocyte activation [129], (iv) Inhibited migration and invasion of fibroblast-like synoviocytes [132], (v) Ameliorated arthritis symptoms [131]; (2).…”
Section: Discussionmentioning
confidence: 99%
“…-anti-inflammatory [128,131], (i) Antifibrosis [128], (ii) Immuno-suppressive [130], (iii) Suppressed excessive granulocyte activation [129], (iv) Inhibited migration and invasion of fibroblast-like synoviocytes [132], (v) Ameliorated arthritis symptoms [131]; (2). -anti-inflammatory [133,134,138], (i) reduced arthritis symptoms [137], (ii) reduced cartilage damage [133,134], (iii) reduced bone erosion [134], (v) Inhibited angiogenesis [134], (vi) Antinociceptive [135,136] 1 Also called: Ledebouriella divaricata (Turcz.) Hiroe.…”
Section: Discussionmentioning
confidence: 99%
“…SINO has been found to modulate immune responses mainly through downregulating the expression of inflammation-related molecules, including NO, TNF-α, IL-1β and prostaglandin E3, both in vitro and in vivo (19)(20)(21). Other studies have demonstrated that SINO exerts its anti-inflammatory role by inhibiting IκB phosphorylation and subsequent NF-κB transcription (22,23). However, the underlying mechanism of action behind the protective effect of SINO in cerebral ischemic injury remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…miR-192 has been reported to be induced or inhibited by different agents. Some agents such as nicotine [48], baicalin [51], sinomenine [52], astragaloside IV [13], captopril and spironolactone [53], paclitaxel [54], and doxorubicin [55] can upregulate miR-192, while other agents including metabolites of intestinal microflora [41], curcumin [56,57], and lactobacillusin [58] can downregulate the expression of miR-192 (Table 5).…”
Section: Discussionmentioning
confidence: 99%